Strategic HR framework for startups: Building sustainable organizations in the digital era - Shinta Winasis; Akbar Firdaus; Agung Terminanto (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
Startups play a crucial role in Indonesia's economy, particularly in driving innovation and creating employment opportunities. With flexible and agile business models, startups offer significant opportunities for young entrepreneurs and the younger generation to develop their careers while contributing to economic growth, especially in the technology sector. However, startups face challenges in organizational governance, particularly in human resource management, leading to significant obstacles in employee retention policies and HR management. This research analyzes strategic challenges in startup HR management and formulates a practical solution framework. Through a systematic literature review of recent publications, the study identifies critical issues, including excessive multi-tasking workloads, unsystematic recruitment processes, limited employee development programs, and high turnover rates. The findings highlight the importance of a holistic, integrative approach that encompasses culture-based recruitment, innovative reward systems, structured mentorship programs, and flexible work environments. Implementing this strategy is expected to build solid, creative teams, laying the foundation for long-term startup sustainability.